Candidate DNA Barcode Tags Combined With High Resolution Melting (Bar-HRM) Curve Analysis for Authentication of Senna alexandrina Mill. With Validation in Crude Drugs - Mishra, Priyanka; Shukla, Ashutosh K.; Sundaresan, Velusamy (Frontiers in Plant Science, 2018)
Senna alexandrina (Fabaceae) is a globally recognized medicinal plant for its laxative properties as well as the only source of sennosides, and is highly exported bulk herb from India. Its major procurement is exclusively from limited cultivation, which leads to risks of deliberate or unintended adulteration. The market raw materials are in powdered or finished product form, which lead to difficulties in authentication. Here, DNA barcode tags based on chloroplast genes (rbcL and matK) and intergenic spacers (psbA-trnH and ITS) were developed for S. alexandrina along with the allied species. The ability and performance of the ITS1 region to discriminate among the Senna species resulted in the present proposal of the ITS1 tags as successful barcode. Further, these tags were coupled with high-resolution melting (HRM) curve analysis in a real time PCR genotyping method to derive Bar-HRM (Barcoding-HRM) assays. Suitable HRM primer sets were designed through SNP detection and mutation scanning in genomic signatures of Senna species. The melting profiles of S. alexandrina and S. italica subsp. micrantha were almost identical and the remaining five species were clearly separated so that they can be differentiated by HRM method .. The sensitivity of the method was utilized to authenticate market samples (Herbal Sample Assays-HSA). HSA01 (S. alexandrina crude drug sample from Bangalore) and HSA06 (S. alexandrina crude drug sample from Tuticorin, Tamil Nadu) were found to be highly contaminated with S. italica subsp. micrantha. Species admixture samples mixed in varying percentage was identified sensitively with detection of contamination as low as 1%. The melting profiles of PCR amplicons are clearly distinct, which enables the authentic differentiation of species by the HRM method. This study reveals that DNA barcoding coupled with HRM is an efficient molecular tool to authenticate Senna herbal products in the market for quality control in the drug supply chain.